The Association Between Influenza Infection Rates and the Incidence of Orofacial Clefts in the United States. (March 2021) - Dymanus, Kyle; Chishom, Taylor; Moraczewski, Jason; Carroll, William; Lima, Maria; Yu, Jack C.; Linder, Daniel
Objective: To investigate seasonal variation of orofacial clefts (OC) and measure association between United States (U.S.) influenza incidences and OC development for the purpose of identifying a potential modifiable risk factor for pregnant women. Design: Retrospective population-based observational study from 2004 to 2013.Setting: National Inpatient Sample Database (NIS), Wide-ranging Online Data for Epidemiologic Research (WONDER) Database, and National Respiratory and Enteric Virus Surveillance System's (NRVESS) FluView database. Patients: U.S.-born infants with OC from 2004 to 2013 and monthly influenza incidence from 2003 to 2013.Main outcome measures: Using logistic regression, monthly odds ratios (OR) of OC were derived using January as baseline. Mixed-effects logistic regression was utilized to test association between national influenza and OC incidences.Results: There were 58 270 U.S. babies born with OC from 2004 to 2013. September births had the highest OC association (OR = 1.094, 95% CI = 1.051-1.138, E -value = 1.41), followed by June. For each additional influenza case per 1000 people, odds of OC event occurring during the 2nd month of pregnancy, or 7 months before delivery, was increased by 2.7 (OR = 2.659, CI = 1.456-4.856, E -value = 4.76). Odds of OC event occurring was decreased at the 3rd month of pregnancy, or 6 months before delivery by 7.8 (OR = 0.129, 95% CI = 0.068-0.246, E -value = 14.99).Conclusion: September and June births have the highest OC association. There is increased risk for OC with influenza occurring at the 2nd pregnancy month. Conversely, there are protective effects against OC with influenza occurring at the 3rd pregnancy month. These findings demonstrate an association between influenza rate and OC, suggesting a connection between maternal immune activation (mIA) and OC. Although further research is needed to determine the definitive link between the use of flu vaccines and OC occurrence, as well as the mechanism behind mIA secondary to influenza infection impacting OC incidence, this study presents a modifiable risk factor that could decrease the potential for mIA causing OC.